Trade Finance, Gaps and the Covid-19 Pandemic: A Review of Events and Policy Responses to Date - Marc Auboin (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Developments in trade finance in 2020 were largely driven by the impact of the COVID-19 pandemic. Twelve years after the great financial crisis of 2008-09, the issue of trade finance re-emerged as a matter of urgency. While the current pandemic-related crisis did not have a financial cause, one of its results has been that many countries are experiencing difficulties in accessing trade credit. This is occurring notably in countries – particularly developing countries – in which structural trade finance gaps were high even before the pandemic. As the health crisis developed and persisted, banks experienced an increase in failures by traders to fulfil payments, including in industries and sectors beyond those initially impacted by lockdowns, such as airlines, aeronautics and tourism. It quickly became evident that one-off extensions of terms of payment by creditors would be insufficient to alleviate the trade finance crisis. Based on the experience of the 2008-09 crisis, governments, export credit agencies and international financial institutions, including multilateral development banks, rapidly intervened to support private markets. Multilateral development banks have provided record amounts of trade finance guarantees and liquidity in developing countries, while governments have implemented payment deferral schemes. Large central banks have supplied foreign exchange resources to other central banks through swap agreements. Efforts to date have been substantial, but challenges remain in 2021, connected first with how to support the importation and exportation of vaccines against COVID-19, and then with how to encourage the recovery of trade flows. Recent events, policy responses and upcoming challenges are discussed and analysed in this paper.
Keywords: F13; F34; G21; G23; 330; trade credit; financial and economic crises; trade